Trends in Marijuana Use among Adolescents in the United States - Jack Yang; Maria C. Mejia; Lea Sacca; Charles H. Hennekens; Panagiota Kitsantas (Pediatric Reports)
Background: Marijuana is a widely used substance in the United States (US) and worldwide. We explored trends in self-reported marijuana use among US adolescents overall as well as by gender, race/ethnicity, and school grade. Methods: Biennial data from the Youth Risk Behavior Survey from 2011 to 2021 included 88,183 adolescents in grades 9th through 12th. We used percentage change as a measure of effect and the chi-square test for significance. All analyses were conducted at the national level. Results: The percentage of adolescents who reported current marijuana use dropped significantly from 23.1% in 2011 to 15.8% in 2021 (p < 0.05). The self-report of trying marijuana for the first time before age 13 also decreased significantly from 8.1% in 2011 to 4.9% in 2021 (p < 0.05). For current use, there were similar significant decreases by race/ethnicity, with Asian, Hispanic, and White adolescents experiencing the steepest declines. In 2021, the percentage of Black adolescents self-reporting marijuana use was significantly higher (20.5%) compared to White (14.8%), Hispanic (16.7%), and Asian (5.1%) adolescents. Although current marijuana use declined significantly for both girls and boys over time, in 2021 girls were more likely (17.8%) to currently use marijuana than boys (13.6%). In 2011, the opposite was true, with boys (25.9%) being more likely to use marijuana than girls (20.1%). Conclusions: In US adolescents in 2021, there were decreases in self-reports of marijuana use compared to 2011. Behavioral interventions within school and family environments may be critical in mitigating the risk of marijuana use.